SISTEM PENGENDALIAN INTERN HUTANG DAGANG PADA FOOD POINT MALL SAMARINDA - -, dona - (EKONOMIA, 2015)
Good internal control system is needed so that the company can achieve the optimal profit or achieve a certain profit level desired. Meanwhile, managing the company's operations are often inconsistent with what has been done, because it is needed by the human resources are skilled and trained to resolve problems faced by the company and is treated a good internal control system which can be used to secure the assets of the company, improve the efficiency of the company, providing reliable accounting information and encourage compliance with established company policies. Implementation of internal control system of trade payables is very important. The problem in this study is whether the internal control system of accounts payable at the Food Point Mall Lembuswana are in accordance with the system of internal control (internal control systems), in theory the research method used is a comparative method and questionnaire. As for the usefulness of this research is the consideration for the leadership of the company, in determining the particular wisdom in the accounts payable system of internal control and as an input and information for management to determine the wisdom. The results showed that the US Food Point Mall Lembuswana samantha has implemented control system properly accounts payable accounts payable due in implementing how many documents are met by the company. Procedures should be a separation of accounts payable section notes payable by the purchasing department. The results were obtained from a variety of data that are primary and secondary, after observing the field as well as by administering a questionnaire, the internal control. Accounts payable internal control system involves some trade-related functions, , but the most important thing that the human individual factors in scrutinizing the shortage. From the analysis and discussion, it can be seen that the accounts payable system Food Point Mall Lembuswana is quite in accordance with the terms of the system of internal control is seen from the results of a questionnaire to get the 78%, which means quite appropriate that the hypothesis is rejected.